Cuidado domiciliar ao homem na perspectiva do atendimento às suas necessidades de saúde - Jocelly de Araújo Ferreira (2018)
The present study starts from the premise that men in situations of vulnerability are evoked in the social conception as domineering and unshakable, besides being treated in mechanistic biomedical vision, centered in the disease, and in the limitations and incapacities of these same men. Therefore, this research established its principles in an integral gender perspective, that is, from the point of view of masculinities. The objective of this study is to analyze the men assisted by home care: to know health needs; investigate the care practices provided; and understand the masculinities presented by men inserted in this context. For a coherent delineation of the theoretical-methodological path of this research, the work is based on the qualitative approach, based on Agnes Hellers epistemological framework of Necessidades (1986) and Necessidades de saúde (1999), by Matsumoto. The analysis was based on a study carried out with the men assisted by the Home Care Service of the city of João Pessoa-Paraíba, as well as their caregivers. The instruments adopted for the production of the empirical material were: the open interview, the observation and the field diary. In order to analyze the empirical data, the methodological reference of the Critical Discourse Analysis was used, having as conceptual base the three-dimensional model of Norman Fairclough. This study was submitted to the Research Ethics Committee of the Federal University of Minas Gerais for analysis and opinion, in accordance with Resolution 466/12 of the National Health Council, under No. 1,829,326. With the critical analysis of the empirical data, the results are divided into four chapters. The first chapter presents the categorization of the social actors of this study, showing the socio-demographic, health and care characteristics of men with health problems from external causes: young adults, single, low schooling, of brown ethnicity, evangelicals and with low family income; while the caregivers, almost all of them female: mothers, with better education when compared to the men, of brown ethnicity, Catholics and dedicating themselves fully to the care of men. The second chapter analyzes the ideologies and contradictions present in the construction of the identity of the male ethos and the consequences for the health needs of the men. It is observed in this chapter that most men presented an ethos with characteristics still hegemonic, while another part of them presented characteristics of a new ethos, conditioned by the differentiation that they experience as a result of their health conditions. The third chapter investigates how the health needs of men assisted by home care persisted in a hegemonic biologist model, but, due to their differentiation, it is possible to identify health needs considered to be counterhegemonic in relation to dominant masculinity, such as: gregarious; have a professional relationship or with the health team; be welcomed and bonded with the caregiver; religiosity; access to health services and technologies; inputs; recreation; digital technology; socialization; accessibility and inclusion. The fourth chapter deals with the reproduced or represented conceptions of care, according to the masculine ethos, establishing a care: feminine and maternal; professional; fragmented; sometimes transferred; reproduced; responsible; co-responsible with affective involvement; and while working. Thus, it is understood that the social construction of masculinities creates obstacles for the recognition of the health needs of the man assisted at home, and that their singularities need to be recognized to contribute to a more integral and equitable health care.